Recurrent mutations of the exportin 1 gene (XPO1) and their impact on selective inhibitor of nuclear export compounds sensitivity in primary mediastinal B‐cell lymphoma. Issue 9 (4th July 2016) - Jardin, Fabrice; Pujals, Anais; Pelletier, Laura; Bohers, Elodie; Camus, Vincent; Mareschal, Sylvain; Dubois, Sydney; Sola, Brigitte; Ochmann, Marlène; Lemonnier, François; Viailly, Pierre‐Julien; Bertrand, Philippe; et al.
Abstract : Primary mediastinal B‐cell lymphoma (PMBL) is an entity of B‐cell lymphoma distinct from the other molecular subtypes of diffuse large B‐cell lymphoma (DLBCL). We investigated the prevalence, specificity, and clinical relevance of mutations of XPO1, which encodes a member of the karyopherin‐β nuclear transporters, in a large cohort of PMBL. PMBL cases defined histologically or by gene expression profiling (GEP) were sequenced and the XPO1 mutational status was correlated to genetic and clinical characteristics. The XPO1 mutational status was also assessed in DLBCL, Hodgkin lymphoma (HL) and mediastinal gray‐zone lymphoma (MGZL).The biological impact of the mutation on Selective Inhibitor of Nuclear Export (SINE) compounds (KPT‐185/330) sensitivity was investigated in vitro . XPO1 mutations were present in 28/117 (24%) PMBL cases and in 5/19 (26%) HL cases but absent/rare in MGZL (0/20) or DLBCL (3/197). A higher prevalence (50%) of the recurrent codon 571 variant (p.E571K) was observed in GEP‐defined PMBL and was associated with shorter PFS. Age, International Prognostic Index and bulky mass were similar in XPO1 mutant and wild‐type cases. KPT‐185 induced a dose‐dependent decrease in cell proliferation and increased cell‐death in PMBL cell lines harboring wild type or XPO1 E571K mutant alleles. Experiments in transfected U2OS cells further confirmed that the XPO1 E571K mutation does not have a drastic impact on KPT‐330 binding. To conclude the XPO1 E571K mutation represents a genetic hallmark of the PMBL subtype and serves as a new relevant PMBL biomarker. SINE compounds appear active for both mutated and wild‐type protein. Am. J. Hematol. 91:923–930, 2016. © 2016 Wiley Periodicals, Inc.